T Cell Defects: New Insights Into the Primary Resistance Factor to CD19/CD22 Cocktail CAR T-Cell Immunotherapy in Diffuse Large B-Cell Lymphoma - Wang, Jiachen; Shen, Kefeng; Mu, Wei; Li, Weigang; Zhang, Meilan; Zhang, Wei; Li, Zhe; Ge, Tong; Zhu, Zhoujie; Zhang, Shangkun; Chen, Caixia; Xing, Shugang; et al. (Frontiers in Immunology, 2022)
Despite impressive progress, a significant portion of patients still experience primary or secondary resistance to chimeric antigen receptor (CAR) T-cell immunotherapy for relapsed/refractory diffuse large B-cell lymphoma (r/r DLBCL). The mechanism of primary resistance involves T-cell extrinsic and intrinsic dysfunction. In the present study, a total of 135 patients of DLBCL treated with murine CD19/CD22 cocktail CAR T-therapy were assessed retrospectively. Based on four criteria (maximal expansion of the transgene/CAR-positive T-cell levels post-infusion [Cmax], initial persistence of the transgene by the CAR transgene level at +3 months [Tlast], CD19+ B-cell levels [B-cell recovery], and the initial response to CAR T-cell therapy), 48 patients were included in the research and divided into two groups (a T-normal group [n=22] and a T-defect [n=26] group).According to univariate and multivariate regression analyses, higher lactate dehydrogenase (LDH) levels before leukapheresis (hazard ratio (HR) = 1.922; p = 0.045) and lower cytokine release syndrome (CRS) grade after CAR T-cell infusion (HR = 0.150; p = 0.026) were independent risk factors of T-cell dysfunction. Moreover, using whole-exon sequencing, we found that germline variants in 47 genes were significantly enriched in the T-defect group compared to the T-normal group (96% vs. 41%; p<0.0001), these genes consisted of CAR structure genes (n=3), T-cell signal 1 to signal 3 genes (n=13), T cell immune regulation- and checkpoint-related genes (n=9), cytokine- and chemokine-related genes (n=13), and T-cell metabolism-related genes (n=9). Heterozygous germline UNC13D mutations had the highest intergroup differences (26.9% vs. 0%; p=0.008). Compound heterozygous CX3CR1I249/M280 variants, referred to as pathogenic and risk factors according to the ClinVar database, were enriched in the T-defect group (3 of 26). In summary, the clinical characteristics and T-cell immunodeficiency genetic features may help explain the underlying mechanism of treatment primary resistance and provide novel insights into CAR T-cell immunotherapy.